Home-Based Learning Activities (H-BLA) In Teaching Physics Topics For Elementary School Students - Candia, Robert; Glomar , Gladys; Joven , Camele; Lasala, Nestor Jr (Journal of Basic Education Research, 2025)
Purpose of the study: This study developed and validated Home-Based Learning Activities (H-BLA) for teaching Physics inspired by the identified Most Essential Learning Competencies (MELCs) by the Department of Education (DepEd). Acknowledging the significance of adaptive and suitable learning materials. Methodology: The researchers employed the descriptive-developmental method to create and assess the developed home-based learning activities. The Learning Resources Management and Development System (LRMDS) evaluation tool of the Department of Education (DepEd) for printed materials is used and experts agreed that the developed H-BLA met the standards for printed learning materials. Main Findings: The findings revealed that the level of validity of H-BLA in terms of content, format, accuracy, and up-to-datedness of information of H-BLA was very much acceptable as validated by the experts supported by the result of factors 1, 2, and 4 being very satisfactory. However, the presentation and organization of H-BLA got a "satisfactory" rating. Novelty/Originality of this study: The study's novelty lies in developing validated Home-Based Learning Activities (H-BLA) for elementary Physics under the K-12 curriculum, utilizing accessible materials to foster independent learning. Grounded in Constructivist Theory, Dale's Cone of Experience, and Contextualized Teaching and Learning, it promotes experiential education. Expert validation and iterative improvement ensure quality, addressing gaps in remote and practical science education